2007
DOI: 10.1002/cne.21615
|View full text |Cite
|
Sign up to set email alerts
|

Early afferent signaling in the outer plexiform layer regulates development of horizontal cell morphology

Abstract: The pedicles of cone photoreceptors, labeled with an antibody to mouse cone arrestin (blue), stratify in the outer plexiform layer, where they form synapses with the dendrites of horizontal and bipolar cells. Those synaptic sites are evidenced by the co‐localization of the synaptic ribbon protein, piccolo (red), with the cone arrestin labeling. The remaining red profiles in the outer plexiform layer indicate the sites of the rod spherules. An antibody to cytochrome oxidase (green) labels the mitochondrion‐rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…1D,F). These latter findings are in agreement with previous studies that observed reduced numbers and abnormally looking/distributed ribbons in photoreceptors of Cav1.4 knockout mice 21,35,[50][51][52][53][54][55][56][57][58] . Data from these previous studies were obtained either from the Cav1.4 knockout mouse model 35,50 that was also analyzed in our study, as well as from other genetically engineered or spontaneous Cav1.4 mouse mutants 51,52,59,60 .…”
Section: Resultssupporting
confidence: 94%
“…1D,F). These latter findings are in agreement with previous studies that observed reduced numbers and abnormally looking/distributed ribbons in photoreceptors of Cav1.4 knockout mice 21,35,[50][51][52][53][54][55][56][57][58] . Data from these previous studies were obtained either from the Cav1.4 knockout mouse model 35,50 that was also analyzed in our study, as well as from other genetically engineered or spontaneous Cav1.4 mouse mutants 51,52,59,60 .…”
Section: Resultssupporting
confidence: 94%
“…Animal models have also allowed for extensive descriptions of physiological changes in response to mutations in Cacna1f . In retinas of all Cacna1f -KO models, synaptic ribbons of the photoreceptor synaptic terminals (discussed above: Ca V 1.4 Function: The Ribbon Synapse and Phototransduction ) never anchor to the presynaptic membrane or elongate into their characteristic morphology, according to electron microscopical and immunohistochemical observations [ 27 , 106 , 117 , 118 ]. Comparisons to CaBP4 -KO and Cacna1f I756T retinas suggest that the synthesis of α 1F protein and the assembly of complete Ca V 1.4 channels in the membrane (regardless of kinetics) are necessary for the initial formation of photoreceptor presynaptic terminals, until P13 after which biophysical properties become important for proper maturation as these models exhibit typical retinal development until eye opening.…”
Section: Insights From Csnb2a Animal Modelsmentioning
confidence: 99%
“…The disruption of the presynaptic terminal and the absence or irregularity of calcium signaling causes complete failure (in loss-of-function [KO]) or severe aberration (in I756T) of synaptogenesis between the photoreceptors and second-order neurons (bipolar and horizontal cells) [ 27 , 102 , 117 , 118 ]. In response, normally rod-connected dendrites of both bipolar and horizontal cells form abnormal extensions into the outer nuclear layer (“sprouting”), and photoreceptor terminals have been reported to retract from the outer plexiform layer into the outer nuclear layer [ 100 , 116 , 118 ].…”
Section: Insights From Csnb2a Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the retina, voltage-gated Ca v 1.4 (L-type) Ca 2ϩ channels are localized in the synaptic terminals of rod and cone photoreceptors where they mediate Ca 2ϩ signals that trigger glutamate release at the first synapse in the visual pathway (1). In mice lacking expression of Ca v 1.4, there is a complete loss of photoreceptor synaptic transmission and a failure in photoreceptor synapse maturation (2)(3)(4)(5)(6). The importance of Ca v 1.4 for vision in humans is illustrated by the disorders associated with mutations in the CACNA1F gene encoding the pore-forming ␣ 1 subunit of Ca v 1.4.…”
mentioning
confidence: 99%